Brief Report: Identification of BACH2 and RAD51B as Rheumatoid Arthritis Susceptibility Loci in a Meta‐Analysis of Genome‐Wide Data. Issue 12 (27th November 2013) - McAllister, Kate; Yarwood, Annie; Bowes, John; Orozco, Gisela; Viatte, Sebastian; Diogo, Dorothée; Hocking, Lynne J.; Steer, Sophia; Wordsworth, Paul; Wilson, A. G.; Morgan, Ann W.; ,; et al.
Abstract : Objective: A recent high‐density fine‐mapping (ImmunoChip) study of genetic associations in rheumatoid arthritis (RA) identified 14 risk loci with validated genome‐wide significance, as well as a number of loci showing associations suggestive of significance ( P = 5 × 10 −5 < 5 × 10 −8 ), but these have yet to be replicated. The aim of this study was to determine whether these potentially significant loci are involved in the pathogenesis of RA, and to explore whether any of the loci are associated with a specific RA serotype. Methods: A total of 16 single‐nucleotide polymorphisms (SNPs) were selected for genotyping and association analyses in 2 independent validation cohorts, comprising 6, 106 RA cases and 4, 290 controls. A meta‐analysis of the data from the original ImmunoChip discovery cohort and from both validation cohorts was carried out, for a combined total of 17, 581 RA cases and 20, 160 controls. In addition, stratified analysis of patient subsets, defined according to their anti–cyclic citrullinated peptide (anti‐CCP) antibody status, was performed. Results: A significant association with RA risk ( P < 0.05) was replicated for 6 of the SNPs assessed in the validation cohorts. All SNPs in the validation study had odds ratios (ORs) for RA susceptibility in the same direction as those in the ImmunoChip discovery study. One SNP, rs72928038, mapping to an intron of BACH2, achieved genome‐wide significance in the meta‐analysis ( P = 1.2 × 10 −8, OR 1.12), and a second SNP, rs911263, mapping to an intron of RAD51B, was significantly associated in the anti‐CCP–positive RA subgroup ( P = 4 × 10 −8, OR 0.89), confirming that both are RA susceptibility loci. Conclusion: This study provides robust evidence for an association of RA susceptibility with genes involved in B cell differentiation ( BACH2 ) and DNA repair ( RAD51B ). The finding that the RAD51B gene exhibited different associations based on serologic subtype adds to the expanding knowledge base in defining subgroups of RA.